2020
DOI: 10.4081/jphia.2020.1131
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with anemia among children aged 6-59 months in Namibia

Abstract: Background: Anaemia remains a public health concern, and the its prevalence varies between countries as well as between age, sex and levels of poverty. This study aims at examining the association between socio-demographic factors and anaemia among children aged 6–59 months in Namibia. Methods: Data was extracted from the 2013 Namibian Demographic Health Survey. The association between anaemia and other factors was examined with logistic regression. Results are reported in odds ratio (OR), with 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…As the wealth index category of women becomes poorer, there is a high likelihood of having anemic children as compared to women with better socio-economic status. This finding was consistent with studies done in sub-Saharan Africa 35 , 36 , Namibia 37 Guinea 38 , Uganda 39 and India 40 . Ethiopia is a poorly developed country and its people rely on seasonal farming.…”
Section: Discussionsupporting
confidence: 92%
“…As the wealth index category of women becomes poorer, there is a high likelihood of having anemic children as compared to women with better socio-economic status. This finding was consistent with studies done in sub-Saharan Africa 35 , 36 , Namibia 37 Guinea 38 , Uganda 39 and India 40 . Ethiopia is a poorly developed country and its people rely on seasonal farming.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the prevalence of anaemia is highest in children ages 1 month to 30 months old compared to all other age groups in the South African population. This correlates to a recent finding in Namibia, where a higher anaemia prevalence was observed among children ages 6–24 months, and that anaemia prevalence decreases with age, possibly because older children can consume more food rich in iron compared to infants [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…One of the studies had strict inclusion criteria resulting in highly selective healthy participants [ 32 ], which could have blurred the true prevalence of anaemia in the studied group. Other studies from African countries showed that younger children of less than 2 years, boys, and children from poorer households have an increased risk of anemia [ 13 , 50 ]. Poor access to health services and inadequate feeding remains important causes of anaemia which could result in impaired physical and intellectual capacity in children later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-thirds of Syrian refugee households were found to live below the poverty line and one-third of households in Lebanon were moderately to severely food insecure [ 12 ]. Existing literature demonstrated that low socio-economic status is associated with a higher burden of anemia among children aged 6 to 59 months [ 13 , 14 , 15 , 16 , 17 ]. In our study conducted in Lebanon in 2018, we found that Syrian refugee children aged 0 to 59 months had two times the odds of being anemic, when the mother was anemic, too.…”
Section: Introductionmentioning
confidence: 99%